ON THE ETIOLOGICAL AND PATHOGENETIC ASPECT OF NONSPECIFIC COLITIS (World Bulletin of Public Health, 2023)
Nonspecific (idiotic) inflammatory bowel diseases are a set of nosological forms of unknown etiology, which are characterized by ulcerative lesions of the walls of the large and/or small intestine as a result of their chronic nonspecific inflammation [25, Error! Bookmark not defined., 2, 9]. Nonspecific ulcerative colitis is based on diffuse ulcerative-inflammatory lesions of the colon, which is clinically manifested by intestinal bleeding, frequent loose stools with an admixture of pus and blood, abdominal pain, tenesmus and constipation
Keywords: Ulcer; Colit; Non-Specific Ulcerative Colitis